Kardiochirurgia wad wrodzonychLung pathology following cardiopulmonary by-pass in patients with Down syndrome (DS) associated with atrioventricular septal defect (AVSD) (preliminary report) - Pietrzykowski, Witold D.; Zieliński, Krzysztof; Siermontowski, Piotr; Moll, Maciej; Moll, Jadwiga; Moll, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
In spite of progress, cardiopulmonary by-pass (CPB) still has a deteriorative effect on the lung. Surgical correction of AVSD improves compliance and respiratory function. However early extubation post operation, especially in patients with DS and AVSD is sometimes impossible. The aim of this study was to determine whether pulmonary tissue in these patients had any lesions as the subject of CPB or any structural abnormalities. Consecutive five patients (aged 3 to 7 months): three with AVSD and DS and two non-DS with AVSD were operated on. Pulmonary biopsies were taken immediately after completing CPB. Analysis was done in 25 randomly chosen microscopic fields. Student and medians tests were used and p<0,05. Patients with DS demonstrated after CPB much more severe intra-parenchymal haemorhagiae, decreased general alveolar number, decreased number of alveoli adjoining to one alveolus and reduced whole parenchymal development, which may suggest a kind of pulmonary tissue hypoplasia.